ELT STUDENTS’ ANXIETY IN LEARNING SPEAKING - Siti Khikmiyah; Imelda Putri (IAI Al-Qolam, 2023)
This research discussed students’ anxiety when learning English. It was conducted to the seventh year English Foreign Language (EFL) Junior High School student of Himmatun Ayat Surabaya. It identified some factors that can cause anxiety when learning English based on students' perspectives. The method used in this research is qualitative with a case study approach. Twenty anxious students were selected as participants. Data were collected through questionnaires and classroom observations. The results of this study show that speaking in front of class, being laughed at by other cryptic comments, students' belief in language learning, teacher's personality and lack of preparation are the factors that contribute to student learning. Students worry when learning English speaking